Somatic-Type Yolk Sac Tumor Arising as a Predominant Component of Bladder Urothelial Carcinoma. (April 2022) - Collins, Katrina; Alkashash, Ahmad M.; Hwang, Michael; Kaimakliotis, Hristos Z.; Cheng, Liang; Idrees, Muhammad T.
Germ cell differentiation has been described in association with somatic tumors arising from several organ systems; rare cases arising from urothelium have been reported. Here we present a 62-year-old male with a remote history of lung cancer, a left adrenal gland mass, and a 5.6 cm left bladder wall mass; cystoscopy demonstrated a large papillary mass on the left anterior bladder wall. A transurethral resection specimen was sent for review in consultation and showed extensive papillary structures with thin fibrovascular cores lined by neoplastic cells with clear cytoplasm. These neoplastic cells were diffusely positive for pancytokeratin, CDX2 (caudal-type homebox 2), SALL4 (sal-like transcription factor 4), glypican-3, AFP (alpha-fetoprotein), while negative for PAX-8 (paired box gene 8), NKX3.1 (NK3 homeobox 1), PSA (prostate specific antigen), TTF-1 (thyroid transcription factor 1), Napsin A, inhibin, and OCT4 (octamer-binding transcription factor 4). Conventional urothelial conventional carcinoma and focal squamous differentiation were also identified as minor components. Urothelial carcinoma was focally positive for GATA3 (GATA-binding protein 3) and p63; SALL4 and glypican-3 were negative. Overall findings supported a yolk sac tumor with a smaller component of squamous cell carcinoma (<1%). Subsequent cystectomy showed similar morphologic features and immunoprofile in addition to foci of urothelial carcinoma and urothelial carcinoma in situ. No chromosome 12p abnormalities were identified by fluorescent in-situ hybridization study. A diagnosis of yolk sac tumor derived from urothelial carcinoma was made. Yolk sac tumor should be considered in the differential diagnosis of a high-grade urothelial carcinoma, particularly when glandular or other unusual architectural patterns are present. A somatic origin with underlying genomic instability similar to what has been described in the uterus and ovaries is suggested.